SPE Improved Oil Recovery Conference 2016
DOI: 10.2118/179684-ms
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of Low IFT Imbibition in Oil-Wet Carbonates

Abstract: Primary and secondary oil recovery from naturally fractured carbonate reservoirs with an oil-wet matrix is very low. Enhanced oil recovery from these reservoirs using surfactants to alter the wettability and reduce the interfacial tension have been extensively studied for many years, but there are still many questions about the process mechanisms, surfactant selection and testing, experimental design and most importantly how to scale up the lab results to the field. We have conducted a series of imbibition exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In addition, researchers have deduced many new imbibition equations based on the consideration of influencing factors like viscosity, IFT, gravity, boundary conditions, surface roughness, slip length, dynamic contact angle, pore shape, etc. [30][31][32][33][34]. Meng et al [35] used the phase-field method to simulate the counter-current imbibition, and the simulation results showed that the imbibition oil recovery was very small in homogeneous porous media but more in heterogeneous porous media, while the difference was closely related to pore structure and size.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, researchers have deduced many new imbibition equations based on the consideration of influencing factors like viscosity, IFT, gravity, boundary conditions, surface roughness, slip length, dynamic contact angle, pore shape, etc. [30][31][32][33][34]. Meng et al [35] used the phase-field method to simulate the counter-current imbibition, and the simulation results showed that the imbibition oil recovery was very small in homogeneous porous media but more in heterogeneous porous media, while the difference was closely related to pore structure and size.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the reservoirs with an average permeability of >0.3 mD can be developed by water flooding, but their ultimate recovery factor is less than 10%. In recent few years, many researchers have been working actively on the ways to improve water flooding, such as surfactant injection and nanofluid injection. Previous research studies indicated that the oil displacement efficiency depends mainly on the imbibition effect generated by capillary force during water flooding of the tight reservoir. , However, the existing surfactants are mostly micron-sized, making them fail to efficiently enter the pores and throats of the tight reservoir matrix. Thus, the field injection–production relationship fails to be built, resulting in serious imbalance of injection and production.…”
Section: Introductionmentioning
confidence: 99%